Pattern of Diseases Presenting in Dermatology OPD of a Tertiary Care Hospital, Kathmandu - Shakya, Sunil; Adhikari, Anurag; Poudel, Ayusha; Aryal, Barun Babu; Jha, Sagar Mani; Shakya, Nabin Bhakta; Dangol, Anil Kumar Singh (Medical Journal of Shree Birendra Hospital, 2019)
Introduction: Dermatological conditions make up a significant burden of hospital visits. This study aims to calculate the prevalence of different dermatological conditions among OPD visits in a tertiary care hospital in Kathmandu, and describe the variation of those conditions with demographic variables and seasons. Methods: This study was performed retrospectively using the data collected in the OPD register of a tertiary level hospital from 14th April 2017 to 13th April 2018. Analysis was conducted using MS Excel 2016 and Statistical Package for the Social Sciences (SPSS) v25. Results: A total number of 24,332 OPD visits were recorded in the year. 54.3% of the visits were made by males and 45.7% by females and most common age group seeking dermatological consultation was 25 to 34 years. Noninfectious dermatoses were more common than infections. The most common noninfectious dermatoses were dermatitis/eczema, urticaria, angioedema and hypersensitivity, and pigmentary disorders in descending order of frequency. The common infectious dermatoses in decreasing order of frequency were fungal, viral, and parasitic/protozoal conditions. The infectious dermatoses were found to be significantly higher in males (p<0.05) while pigmentary disorders, urticaria and angioedema, autoimmune cutaneous disorders, disorders of pilosebaceous units and xerosis were significantly higher in females (p<0.05). Bacterial, fungal and viral infections, eczemas, urticarial/angioedema, papulosquamous disorders, xerosis, neoplasms and vasculitis showed significant seasonal variation. Conclusions: Eczemas and fungal infections are the most common dermatoses. Infectious dermatoses and several non-infectious dermatoses vary significantly with seasons.